Survei Tingkat Kebugaran Jasmani Siswa Tunarungu di SDLB Putra Pancasila - Bakri Khotib; Luthfie Lufthansa; Yulianto Dwi Saputro; Ary Artanty; Laila Nur Rohmah (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to describe the physical fitness levels of deaf students at SDLB Putra Pancasila. Materials and methods. The method used was a descriptive survey with data collection techniques in the form of physical fitness tests that have been adapted for children with special needs, such as the Eurofit test, which includes the Bent Arm Hang Test, Sit & Reach, Harvard Step Test, 50-metre run, and Flamingo Balance Test. Results. The survey results indicate that most deaf students at SDLB Putra Pancasila fall into the low to moderate physical fitness category. This finding aligns with similar studies at other special schools, which suggest that low daily physical activity levels and limited sports facilities also influence the physical fitness outcomes of deaf students. Conclusion. This study recommends the need to enhance adaptive physical education programmes and provide adequate sports facilities to support improvements in the physical fitness of deaf students at SDLB Putra Pancasila.